Deep-sea nematodes of the family Microlaimidae from the Clarion-Clipperton Fracture Zone (North-Eastern Tropic Pacific), with the descriptions of three new species - Miljutin, D. M.; Miljutina, M. A. (Zootaxa, 2009)
The description of six species of family Microlaimidae (Nematoda), from 5,000 m depth at the Clarion-Clipperton Fracture Zone (North-Eastern Tropic Pacific), is given. Three previously described species (Microlaimus discolensis Bussau et Vopel, 1999; M. porosus Bussau et Vopel, 1999; and Caligocanna mirabilis Bussau et Vopel, 1999) were found about 5200 km far from the area where the type specimens were originally discovered (the Peru Basin, South-East Pacific). Of the new species, Aponema martinezi sp. n. is closest to two other Aponema species, A. minutissima Kovalyov and Miljutina, 2008 and A. nanum (Blome, 1982). However, it differs from them in having a non-set-off head, amphids located quite far from the non-annulated cephalic capsule, and by possessing the gubernaculum with the apophysis. Microlaimus abyssalis sp. n. belongs to a group of Microlaimus species with dorsocaudal apophyses of gubernaculum. It differs from other four Microlaimus species which have apophyses of similar shape (M. crassiceps Gerlach, 1953; M. decraemerae (Muthumbi & Vincx, 1999); M. mnazi (Muthumbi & Vincx, 1999); and M. undulates Gerlach, 1953) by lacking of supplementary precloacal organs in males and some other body parameters. Microlaimus parviporosus sp. n. possesses four submedian rows of pores along its entire body length. In this feature it resembles three other Microlaimus species (M. cyatholaimoides de Man, 1922; M. discolensis Bussau and Vopel, 1999; and M. porosus Bussau and Vopel, 1999). The new species differs from M. cyatholaimoides and M. porosus by the ratio of the length of the outer labial setae and of the cephalic setae (approximately of equal length in the new species vs. the much longer cephalic setae in two latter species) as well as some other parameters. The new species differs from M. discolensis by its shorter head setae of two rings (1.2 mu m vs. 6-9 mu m) and some other parameters.
NeMys doc_id: 17914